GNSS Real-Time Kinematic Positioning Theory and Applications - Li, Bofeng; Zhang, Zhetao; Miao, Weikai; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2025)
This open access book presents the high-precision Real-Time Kinematic (RTK) positioning technique of global navigation satellite systems, including its development, principle, implementation, applications and recent innovations. As the highlights of this book, various extensions of the RTK technique are introduced with emphasis on their features to overcome different challenges of different applications. The applications include the positioning with few reference stations available in a large scale of area, the positioning requiring instant convergence, the positioning at sea without normal communication, the high-precision positioning and attitude determination of rigid objects, the positioning with low-cost chip in the canyon environments. The mathematical models of different extended RTK techniques are derived in a unified framework. The characteristics of different RTK extensions are vividly compared with each other based on diagrams. The demonstration application and experimental results of each RTK extension are introduced. In brief, this book provides comprehensive outdoor high-precision positioning solutions for different scientific, engineering and social applications. It is suitable for readers who need or are interested in the high-precision positioning technique.
Overview -- GNSS Error Effects in RTK -- Optimal Estimation in RTK -- Integer Ambiguity Resolution -- Cycle Slip and Data Gap Repair -- Stochastic Modelling -- Unmodeled Error Processing -- Data Quality Control -- LRTK: Long-range RTK -- ERTK: RTK with Multi-frequency Signals -- ORTK: RTK Based on BDS Short-message Communication -- ARTK: Antenna-Array Aided RTK -- CRTK: cost-effective RTK.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Signal processing; Telecommunication; Signal, Speech and Image Processing; Communications Engineering, Networks